Lean Six Sigma principles and practices under a management perspective - Juliani, Fernando [UNESP]; de Oliveira, Otávio José [UNESP] (Taylor & Francis, 2019)
The purpose of this paper is to systematise principles and practices of the Lean Six Sigma (LSS) method to encourage and facilitate its implementation and management in different contexts. The construction of LSS principles and respective practices was based on grounded theory and supported by analysis of both most cited keywords in LSS literature and scientific gaps raised in LSS literature reviews. The LSS systematised principles and respective practices are presented in a descriptive and schematic manner, homogenising the theoretical basis for the development of new researches. This may assist researchers in developing new literature reviews, case studies and guidelines applicable to both specific and general business areas. In addition, this LSS review can contribute to the knowledge of the organisation’s professionals by providing insights and raising relevant issues to be addressed when implementing LSS in different contexts, allowing managers to make better decisions.
Keywords: Lean Six Sigma; LSS principles and practices; management; systematisation